2022
DOI: 10.3389/fmicb.2022.1030833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum KSFY01 on the exercise capacity of D-galactose-induced oxidative stress-aged mice

Abstract: ObjectivesAging is a process that involves comprehensive physiological changes throughout the body, and improvements in the exercise capacity of individuals may delay aging and relieve fatigue. Probiotics are subject to ongoing research to investigate their antioxidant properties. The purpose of this study was to investigate the effect of the probiotic Lactobacillus plantarum KSFY01 (L. plantarum KSFY01) on exercise tolerance in mice induced into a state of accelerated physiological aging by oxidative stress.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…When it comes to exercise-related gut disorders, probiotic supplements emerge as a promising possibility for enhancing gut microbial composition and boosting exercise performance [12 ]. Previous studies suggest that probiotics, such as Lactobacillus plantarum, can enhance glycogen stores in mice [49], while Saccharomyces boulardii has been found to optimize physical performance [50]. Recent experiments isolating bacteria from Olympic athletes, even noted antifatigue effects in supplemented mice [51].…”
Section: Strategies For Manipulating the Microbiome In Athletesmentioning
confidence: 99%
“…When it comes to exercise-related gut disorders, probiotic supplements emerge as a promising possibility for enhancing gut microbial composition and boosting exercise performance [12 ]. Previous studies suggest that probiotics, such as Lactobacillus plantarum, can enhance glycogen stores in mice [49], while Saccharomyces boulardii has been found to optimize physical performance [50]. Recent experiments isolating bacteria from Olympic athletes, even noted antifatigue effects in supplemented mice [51].…”
Section: Strategies For Manipulating the Microbiome In Athletesmentioning
confidence: 99%
“…Recently, there has been an increasing number of studies evaluating the effects of probiotics, such as lactic acid bacteria and bifidobacteria, in aged or aging-induced mice, and there is growing evidence that sarcopenia can be prevented by administering probiotics [90][91][92][93]. In addition, a review and meta-analysis of human randomized controlled trials reported by Prokopidis et al showed that probiotic supplementation enhanced both muscle mass and strength [94].…”
Section: Probiotic Effectsmentioning
confidence: 99%
“…In these experiments, probiotic supplementation led to a decrease in lactate, ammonia and creatine kinase [ 95 , 96 ]. Other strains, such as Lactobacillus plantarum (TWK10; from pickled vegetables) and Lactobacillus plantarum (KSFY01; from yak yogurt), increased glycogen storage, muscle mass and strength, and time to exhaustion in mice [ 97 , 98 ]. In rats, Bacillus subtilis (BSB3) was found to prevent negative changes in the gut caused by excessive exercise, and Saccharomyces boulardii (Sb) led to aerobic performance enhancement [ 99 , 100 ].…”
Section: Prebiotics Probiotics and Gut Microbiota—animal Studiesmentioning
confidence: 99%